Raseinių rajono viešosios bibliotekos knygos muziejus - Brigys, Jonas (Knygotyra, 2003)
In 1992 the whole former building of Raseiniai district culture house was transferred to the public library so there were real conditions to found a Book museum. At the beginning of 1995 the museum was opened to the first visitors. Since the establishment of the Book museum Elena Kvietkienė, the senior bibliographer responsible for local lore studies, runs the museum and receives visitors. At the end of 1995 our rather moderate exposition was enriched with Lithuanian philological publications printed before 1940 from the reserve stock of the Centre of Bibliography and Book Lore of Lithuanian National Library. More than 5000 ancient printed matters have been received. They not only enriched the exposition of the Book museum, but also allowed to form a stock of old and rare printed matters. Besides, some support came from foreigners, whose birthplace in Raseiniai district. About 4000 printed matters were presented to the library by S. Džiugas alone.It has been decided that the museum exposition will be historical and literary-educational. The fact that literature of local lore studies becomes more and more popular encouraged the library to devote a large part of the exposition to the displays which reflect the literary life of our land and its history. Lots of attention is granted to Maironis, the famous poet of Raseiniai land. The stands dedicated to the poet occupy half of the exposition of the Book museum. While establishing this part of the exposition, we collaborated with Maironis Lithuanian Literature Museum. In addition, the board of Raseiniai district administration financially supported the project. Nor large expositions are devoted to other writers and poets of Raseiniai land, such as J. Aputis, J. Mačiukevičius, M. Martinaitis, D. Teišerskytė and the club of district authors, called Dubysa. The old writers and poets M. S. Slavočinskis, S. Stanevičius, A. Fromas-Gužutis others are not so widely presented because of the shortage of authentic exhibits.Quite a lot of space on the museum stands is occupied by the exposition "The Route of the Lithuanian Book". The original publications and the space on the stands predeterminated the chronological frames (XVIIth century – the beginning of XXth century).Unfortunately, the Lithuanian book of the XVIIIth century is presented by Polish and Latin books only. Farther exposition is assigned to publications printed in the USA in the first half of the XIXth century (until the prohibition of Lithuanian press). This book lore exposition increased when the Book museum received editions pressed in Raseiniai printing-house which functioned till 1941.Apart from the continuous exposition, the Book museum organizes yearly topical exhibitions mostly dedicated to literary anniversaries. A numerous stock of old and rare printed matters allows to exhibit them not only in the Book museum of Raseiniai district public library.Old books and periodical press adorn other exhibitions organized in the library. Several wide topical exhibitions have been organized in the Art showroom of the library and the History museum of Raseiniai land. The stock of ancient and rare pressed matters owns more than 300 books with autographs and dedications. This fact also allows to show the Lithuanian book and its route in a different light. Among them there are some very interesting copies which belonged to some peasants libraries during the times of press prohibition or witness the tragedy of Holocaust.While organizing exhibitions in the Book museum rare publications are often hired from K. Grikšas rich personal library.The exposition of the museum fulfils not only informative function of preservation and popularization of the heritage, but also it allows the readers to use its stock of valuable publications. Apart from the largest History museum of Raseiniai land, Raseiniai district has several smaller museums perpetuate Maironis, S. Stanevičius remembrance. On the other hand, not all authors whose birthplace is Raseiniai district have been properly honoured, so the Book museum tries to compensate this reflecting their creative work. On the whole, the Book museum fulfils not only the educational function of representing the history of the Lithuanian Book and its evolution, but also is an integral part of the museums presenting Raseiniai land and its authors.